Frailty screening of Tunisian older adults: feasibility and usefulness in the Emergency Department - Chakroun-Walha, Olfa (Afr J Emerg Med, 2020)
INTRODUCTION: Frail older adults are at an increased risk for adverse outcomes after an Emergency Department (ED) visit. Several tools exist for the screening of frailty among these patients. However, no tool has been validated in Tunisia. This study aims to evaluate the usefulness of frailty screening in predicting the outcome of older adults presenting to the ED. METHODS: This is a prospective, monocentric study. We evaluated the eligible patients at the ED and after their discharge. Follow-up phone calls were scheduled at 1, 2, 3, and 6 months after the ED visit. All patients aged 65 years or older; and visiting the ED during the inclusion period were involved. We used the ADL index and ISAR scale for assessing frailty. RESULTS: We enrolled 184 patients; they were living alone in 25% of cases. Half of them had medical care insurance. The ADL index was maximum (6 = total dependency) in 20% of cases. The ISAR score was above 1 point in 38%. Unplanned hospitalizations have accounted for 34%. In univariate analysis, the ADL index and ISAR score were statistically higher in the group of “unplanned hospitalization”. In multivariate analysis, the ISAR score and ADL index have not been associated with unplanned hospitalization. CONCLUSION: Our results did not demonstrate the relevance of the ISAR or ADL scales in predicting the mortality or the need for unplanned hospitalization in multivariate analysis. This study did indicate an increased mortality in the “frail” patients in the univariate analysis. Further studies with larger samples and different tools are necessary.